The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/es103518c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Elemental Carbon in Lake Sediments Measured by Three Different Methods and 150-Year Pollution History in Eastern China

Abstract: Concentrations of elemental carbon (EC) were measured in a 150 yr sediment record collected from Lake Chaohu in Anhui Province, eastern China, using three different thermal analytical methods: IMPROVE_A thermal optical reflectance (TOR), STN_thermal optical transmittance (TOT), and chemothermal oxidation (CTO). Distribution patterns for EC concentrations are different among the three methods, most likely due to the operational definition of EC and different temperature treatments prescribed for each method. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 36 publications
2
97
0
Order By: Relevance
“…For quality assurance and quality control (QA/QC), whether the residue on the filters has an even distribution is a primary factor that markedly influences the accuracy of the BC concentration determination (Khan et al, 2009;Han et al, 2011;Fang et al, 2015). The typical filters loaded with acid-treated sediment residue are displayed in Fig.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…For quality assurance and quality control (QA/QC), whether the residue on the filters has an even distribution is a primary factor that markedly influences the accuracy of the BC concentration determination (Khan et al, 2009;Han et al, 2011;Fang et al, 2015). The typical filters loaded with acid-treated sediment residue are displayed in Fig.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…In this study, char and soot were measured using the IMPROVE thermal optical method according to Han et al (2007b), which has been validated and successfully applied in aerosol studies (Han et al, 2010;Lim et al, 2012) and in soil and sediment studies (Han et al, 2009(Han et al, , 2011(Han et al, , 2015a(Han et al, , 2015bCong et al, 2013), in order to yield a better understanding of the distribution, sources and potential input pathways of char and soot within the tropical coastal system in SE Asia.…”
Section: Occurrence and Input Pathways Of Char And Soot In The Gotmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely that industrial emissions, especially those from coalpowered metal smelters in Huangshi, led to high accumulation rates for fossil BC over the past several decades. This type of influence can be seen in the historical variations of char/soot ratio in sediments from Lake Chaohu, eastern China (Han et al, 2011). Moreover, exhaust emissions from motor vehicles can lead to high BC deposition rates in urban areas-this has been shown in studies of both aerosols and sediments.…”
Section: Bc Deposition and Environmental Implicationsmentioning
confidence: 90%
“…Moreover, exhaust emissions from motor vehicles can lead to high BC deposition rates in urban areas-this has been shown in studies of both aerosols and sediments. For example, by using the TOR method, Han et al (2011) found that the variations of soot in the sediments from Lake Chaohu increased after 1978, corresponding with the growth in the total number of motor vehicles.…”
Section: Bc Deposition and Environmental Implicationsmentioning
confidence: 99%